Gender-specific epidemiology of diabetes: a representative cross-sectional study - Taylor Anne W; Hicks Neville; Grant Janet F; Chittleborough Catherine R; Phillips Patrick J (International Journal for Equity in Health, 2009)
Abstract Background Diabetes and its associated complications are part of a chronic disease global epidemic that presents a public health challenge. Epidemiologists examining health differences between men and women are being challenged to recognise the biological and social constructions behind the terms 'sex' and/or 'gender', together with social epidemiology principles and the life course approach. This paper examines the epidemiology of a population with diabetes from the north-west metropolitan region of South Australia. Methods Data were used from a sub-population with diabetes (n = 263), from 4060 adults aged 18 years and over living in the north-west suburbs of Adelaide, South Australia. Eligible respondents were asked to participate in a telephone interview, a self-report questionnaire and a biomedical examination. Diabetes (undiagnosed and diagnosed) was determined using self-reported information and a fasting blood test administered to participants. Data were analysed using SPSS (Version 10.0) and EpiInfo (Version 6.0). Results Factors associated with diabetes for both men and women were being aged 40 years and over, and having a low gross annual household income, obesity and a family history of diabetes. In addition, being an ex-smoker and having low cholesterol levels were associated with diabetes among men. Among women, having a high waist-hip ratio, high blood pressure and reporting a previous cardiovascular event or mental health problem were associated with diabetes. Conclusion The results found that men and women with diabetes face different challenges in the management of their condition. Public health implications include a need for quality surveillance data, including epidemiological life course, social, behavioural, genetic and environmental factors. This will enrich the evidence base for health promotion professionals and allow policy makers to draw inferences and conclusions for interventions and planning purposes.